Characteristics of the dynamic stands of aviation simulators - Кабанячий, В. В. (Proceedings of National Aviation University (archive), 2020)
The method of determination of dynamic characteristics, which allows to estimate the suitability of dynamic stands to simulate accelerated acts on aviation simulators, is presented.